DETERMINANT OF HUMAN DEVELOPMENT WITH THE MAQASID SHARIA CONCEPT IN JAVA ISLAND - Nunung Robiatul Rifkah; Qi Mangku Bahjatullah (Jurnal Ekonomi, 2023)
This study aims to determine the effect of the level of education and health on human development using the Islamic Human Development Index based on Maqasid Syariah in Java Island in 2016-2021. This research is a quantitative study using a sample of 6 provinces on the island of Java with an observation period of 2016-2021. The type of data used is secondary data in the form of official statistical reports from government agencies. The analytical method used is multiple regression analysis assisted by Eviews9 software. The results showed that economic growth had a significant positive effect on IHDI, the education function had no significant negative effect on IHDI, the health function had no significant positive effect on IHDI and unemployment had a significant positive effect on IHDI.